Investigating Student Perceptions Based on Gender Differences Using E-Module Mathematics Physics in Multiple Integral Material - Astalini Astalini; Darmaji Darmaji; Dwi Agus Kurniawan*; Diki Chen (Universitas Syiah Kuala, 2021)
Mathematics physics is a difficult learning and becomes a scourge in studies in physics education. Learning physics and mathematics itself will be very effective when using e-modules, but in terms of making e-modules, students' opinions or perceptions are needed regarding this matter. This study aims to look at student perceptions and also compare these perceptions with other classes based on gender or gender. The research conducted is a survey type quantitative research. The sampling technique used in this study was simple random sampling with the research subject as many as 92 physics education students who contracted the mathematics physics course. The instrument used in collecting data is 15 questions containing 4 choices that must be filled out by students. Analysis of the data used in this study in the form of descriptive analysis and ANOVA test to determine whether there is an average difference in each student's perception. The results obtained indicate that girls have different perceptions in class A and class B, while for boys there is a difference between class A and class C. These results indicate that girls have a fairly large average difference in perception with each other, while for boys the perception tends to be uniform compared to girls.